Rapid method for assessing relative tissue stiffness using MR acoustic radiation force imaging. Issue 1 (March 2014) - Hertzberg, Yoni; Hugeri, Mali; Navon, Gil; Azhari, Haim
ABSTRACT Acoustic radiation force imaging (ARFI) has been suggested as a tool for remote palpation. In this study an MR‐ARFI sequence, based on echo‐planar‐imaging, is introduced, for remote semi‐quantitative assessment of local tissue stiffness. The focal zone of a high intensity focused ultrasound (HIFU) is positioned at the region of interest and a single HIFU burst is transmitted. The method then measures the entire time integral of the resulting displacement at the focal zone. Combining this measurement with the Kelvin–Voigt viscoelastic tissue model, a local stiffness index is obtained. The method was implemented on gel phantoms, ex‐vivo bovine brain and chicken liver specimens. The results have demonstrated the ability to evaluate the relative local stiffness within 600 ms and to distinguish between different tissues on the basis of their stiffness index. The method may potentially be used for remote palpation of suspicious regions for diagnostic purposes, or for providing a mechanical feedback during therapeutic procedures, such as thermal ablation.